Lithuania’s National Digital Health System Architecture, Evolution, and Lessons From a Centralized Approach Using Longitudinal Document Analysis: Descriptive National Case Study - Austėja Dapkutė; Olegas Niakšu; Julius Juodakis; Danguolė Jankauskienė; Justas Trinkūnas; Arvydas Laurinavičius; Tomas Jovaiša; Donata Ringaitienė; Martyna Atraškevičienė; Rytis Masiliūnas (JMIR Formative Research, 2026)
Background National digital health systems are increasingly recognized as a key tool for strengthening health care systems and improving patient outcomes. Global guidance from the World Health Organization and European Union initiatives emphasizes interoperability, robust data governance, and secure exchange of health information as prerequisites for system-wide benefits. However, translating these principles into operational national digital health infrastructures remains challenging, and empirical evidence on long-term, centralized implementation models is limited. Lithuania is among a small number of European countries that have implemented a fully centralized national digital health platform (DHP), providing a valuable case for examining the development, structure, and performance of such systems. Objective This study aimed to describe and analyze Lithuania’s national digital health system across its historical development, governance, technical architecture, interoperability and adoption, and to identify challenges and lessons learned. Methods We conducted a descriptive national case study of Lithuania’s digital health system using longitudinal document analysis. Publicly available policy documents, legislation, strategy reports, audits, and official statistics published between 2000 and 2025 were systematically reviewed following the readying, extracting, analyzing, and distilling (READ) framework. Thematic analysis was applied to examine governance, system architecture, interoperability, adoption, and implementation challenges. Peer-reviewed literature was used for contextualization. Results Lithuania’s digital health system evolved from fragmented initiatives in the early 2000s into a fully centralized national DHP that has been operational nationwide since 2015. Since 2018, health care providers have been required to record core clinical data electronically, and all reimbursed medicines are prescribed exclusively through the national electronic prescription system. The DHP integrates electronic health records, electronic prescription system, appointment booking, and other national subsystems with standardized interfaces. System use expanded rapidly: the annual number of electronic documents stored in the DHP increased from approximately 7 million in 2017 to over 100 million in 2024, reflecting widespread uptake of outpatient documentation, referrals, and prescriptions. Patient-facing services, including online access to records and a nationwide appointment booking system, also expanded, although patient-initiated use remains uneven across regions. The platform supports secure primary use for care delivery and secondary use of health data through a centralized access pathway. While core services have reached national scale, some subsystems, such as imaging exchange and telemedicine, remain less mature. Ongoing modernization focuses on improving data interoperability, enabling advanced analytics and future AI-based services, strengthening cross-border eHealth services, and extending coverage to sensitive and previously excluded domains such as mental health, maternal, and newborn care through dedicated subsystems. Conclusions Lithuania’s centralized digital health system illustrates both the potential and the limitations of national-scale integration driven by legal mandates and standardized interoperability. Its experience provides transferable insights for health systems seeking to consolidate fragmented infrastructures while maintaining data security, regulatory compliance, and long-term system adaptability.